Pengembangan Modul Termokimia Berbasis Inkuiri Terbimbing Terintegrasi Eksperimen untuk Kelas XI SMA/ MA - Andromeda, Alfirahmi, (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Thermochemistry is a topic which consists of abstract concepts that makes itharder to be understood by students. But students can understand it if they were guidedto build their knowledge by finding the concepts by themselves and putting student’ assubject of the study. An instructional learning model that can be used to learn this topicbased on it is characteristic is guided inquiry model. This study aims to develop a thermochemistrymodule based on inquiry integrated with experiments for senior highschool students’ and to determine validity and practicality category of the developedproduct. The research type was Research and Development (R&D) with 4-D model,which will resulted a specific product. 4-D model consists of four steps, Define, Design,Develop, and Disseminate. This study performed validity and practicality test only. Theinstrument were validity and practicality questionnaire. Data collecting technique weredisseminated the questionnaire and the analysis of the result were done using KappaCohen formula. Based on the analysis of the validity questionnaire, Kappa moment valueobtained was 0.81 which considered as very high and from the analysis of practicalitytest from teachers and students were 0.93 and 0.81 respectively. It can be concludedthat the developed thermochemistry module based on guided inquiry integrated withexperiments is valid and practice to used on a learning process.Keywords : guided inquiry, module, research and development, thermochemistry, 4-Dmodels